IMPACT OF TOURISM ON JAMMU & KASHMIR ECONOMY - Iqbal, Junaid (International Journal of Research -GRANTHAALAYAH, 2021)
Tourism across the world is playing a great role in building the economies. Tourism is widely used for building the economic development and economic prosperity around the globe. Tourism sector is growing day by day and helping nations to build the economic prosperity of the country. Nations around the world are investing lot of money in building great infrastructure for tourism, so that they can attract tourists from around the world. & Kashmir is one of the leading tourist destinations where tourists love to be. It is that around 50%-60% people of the state are directly or indirectly related with the tourism. and Kashmir economy is a service economy where majority of revenue is coming from tourism sector. In this paper the topic of discussion was to know the impact of tourism on Jammu and Kashmir economy. Apart from that simple regression is used to know the impact of tourism on economy while taking the factors like GDP, EMPLOYMENT and PER-CAPITA INCOME. The results of the analysis were very tremendous it shows that tourism has significant impact on the factors which has been taken as a part of paper. There is a need to build more facilities and to work on some flaws. Tourists around the world love to visit the state because the state is blessed with the beauty of nature. The state should focus towards the infrastructure development so that more and more tourists visit every year.